Pengaruh Meal Experience Terhadap Kepuasan Pelanggan Di D’riam Riverside Resort And Resto - Restu Rahayu, Riksa; Setiyorini, HP. Diah; Ryana, Hery (Universitas Pendidikan Indonesia, 2016)
Bandung is one of the city's rapid development of its restaurant. Restaurant types ranging from the western, specialty restaurant, etc. Bandung is synonymous with a distinctive flavor that Sunda in Bandung are found restaurants of Sundanese one is d'Riam Riverside Resort.The number of purchases at d'Riam Reverside Resort or the ups and downsexperienced fluctuating revenue (gross revenue) in each year starting in 2012-2014. Good management is needed to boost consumer visits to d'Riam Reverside Resort.Aims this study are (1) To obtain research findings about consumer response to meal experiance in d'Riam Riverside Resort, (2) To obtain research findings on customer satisfaction in d'Riam Reverside Resort, (3) To obtain research findings on the effect of meal experiance on customer satisfaction. The research method used is descriptive and verificative, while the data collection techniques with questionnaires to 100 respondents.Results of the study concluded that of the seven sub-variables meal experiencenot all variables are positive and significant impact on customer satisfaction as a variable interior design and the other six are food and beverage, variety in menu choice, level of service, price and value for money, atmosphere, location and accessibility are very positive and significant effect between meal experience of customer satisfaction.